PENGARUH LIKUIDITAS, PROFITABILITAS, UKURAN PERUSAHAAN DAN PERTUMBUHAN PENJUALAN TERHADAP STRUKTUR MODAL PADA PERUSAHAAN SUB SEKTOR OTOMOTIF DAN KOMPONEN YANG TERDAFTAR DI BEI PERIODE 2011-2015 - -, Novi Sariani (EKONOMIA, 2018)
The purpose of this study to determine 1. The influence of liquidity on capital structure. 2. Effect of profitability on capital structure. 3. Effect of firm size on capital structure. 4. The influence of sales growth on capital structure. 5. Effect of liquidity, profitability, firm size and sales growth on capital structure.The formulation of the problem of this research is 1. Does liquidity have significant effect to capital structure. 2. Whether profitability has a significant effect on capital structure. 3. Does the size of the company significantly affect the capital structure. 4. Do sales growth significantly affect the capital structure. 5. Is liquidity, profitability, firm size and sales growth significantly affect the capital structure. Basic Theory of Financial Management that focuses on liquidity, profitability, firm size, sales growth and capital structure. Hypothesis of this research is 1. Liquidity have significant effect to capital structure. 2. Profitability has a significant effect on capital structure. 3. The size of the company has a significant effect on capital structure. 4 sales growth has a significant effect on capital structure. 5. Liquidity, profitability, firm size and sales growth have a significant effect on capital structure.The sample used is 6 companies. Sample selection method used is purposive sampling method. Analyzer used is multiple linear regression analysis.Â  Based on the results of research of the independent variables studied in the automotive sub-sector companies and components listed on the Indonesia Stock Exchange: 1. Liquidity has no significant negative effect on capital structure. 2. Profitability has no significant negative effect on capital structure. 3. Size of the company has a positive effect is not significant on capital structure. 4. The growth of sales positively insignificant effect on capital structure. 5. Liquidity, profitability, firm size and sales growth have no significant effect on capital structure.